2020
DOI: 10.1039/d0fo01282c
|View full text |Cite
|
Sign up to set email alerts
|

Fubrick tea attenuates high-fat diet induced fat deposition and metabolic disorder by regulating gut microbiota and caffeine metabolism

Abstract: Fubrick tea aqueous extract (FTEs) improved lipid metabolism by regulating gut microbiota and caffeine metabolism in high-fat diet induced obese mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 84 publications
3
43
0
Order By: Relevance
“…Our results indicated that a high-fat model was successfully established by feeding SD rats with a high-fat diet for four consecutive weeks. In the present study, the increase in serum and liver lipid levels in rats fed a high-fat diet was consistent with other studies [ 8 , 50 , 51 ]. However, the serum and liver lipid levels of HFD rats supplemented with walnut meal peptides were restored to levels close to those of ND rats.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that a high-fat model was successfully established by feeding SD rats with a high-fat diet for four consecutive weeks. In the present study, the increase in serum and liver lipid levels in rats fed a high-fat diet was consistent with other studies [ 8 , 50 , 51 ]. However, the serum and liver lipid levels of HFD rats supplemented with walnut meal peptides were restored to levels close to those of ND rats.…”
Section: Discussionsupporting
confidence: 93%
“…Previously reported, the abundance of Parabacteroides was signi cantly decreased in obese subjects with metabolic syndrome [6], and nonalcoholic fatty liver disease [25], and negatively correlated with weight gain and leptin plasma levels [26]. And germane to our ndings, both genera Gemmiger [27] and Parabacteroides [28] are gut bacteria negatively associated with obesity and disturbed host metabolism. In accordance, we found that that the fecal abundance of these bacteria was signi cantly higher in the MHO group compared with MUO.…”
Section: Discussionsupporting
confidence: 78%
“…Ruminococcus_torques_groupis a genera derived from genus Mediterraneibacter from the family Lachnospiraceae (NCBI Taxonomy Browser, https://www.ncbi.nlm.nih.gov/ Taxonomy/Browser/wwwtax.cgi) and was discovered to ferment gastric mucins and identified as a butyrate-producing bacterium (41). A study on Fubrick tea aqueous extract (FTEs) in mice indicated that FTEs were able to alleviate visceral fat deposition via an increase in the abundance of Lachnospiraceae (42). This result suggests a positive correlation between fat deposition and Lachnospiraceae abundance.…”
Section: Discussionmentioning
confidence: 99%